Understanding IoT Privacy Policies: Perceptions and Concerns of College Students Regarding Data Security - Fadhlirrahman Baso (Information Technology Education Journal, 2025)
The development of Internet of Things (IoT) technology presents new challenges related to personal data protection. Among university students, the use of IoT devices is increasing, yet their understanding of privacy policies remains low. This study aims to analyze students’ understanding of IoT application privacy policies and their impact on personal data security. A quantitative descriptive approach was employed, utilizing an online questionnaire filled out by student respondents. The data analysis results indicate that the proportion of students who rarely read privacy policies and have limited understanding of them is relatively high. Only 22.65% of respondents reported regularly reading privacy policies, 20.55% demonstrated an understanding of privacy policies, and 20.27% expressed concern about the misuse of personal data. These findings indicate that most students do not read IoT application privacy policies, resulting in a relatively low level of concern about potential data misuse. Therefore, more accessible and comprehensible privacy policies are necessary to improve privacy literacy and enhance user trust in IoT mobile applications. Clearer privacy policies and increased education on the importance of privacy are essential to improve digital literacy and strengthen user confidence.